2016
DOI: 10.1182/blood-2015-09-672774
|View full text |Cite
|
Sign up to set email alerts
|

Anti–factor VIII IgA as a potential marker of poor prognosis in acquired hemophilia A: results from the GTH-AH 01/2010 study

Abstract: Key Points This study is the first to assess the prognostic value of FVIII-specific antibody data in patients with AHA. Anti-FVIII IgA, but not immunoglobulin G, autoantibodies at baseline are potential predictors of recurrence and poor outcome of AHA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
56
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(70 citation statements)
references
References 26 publications
7
56
1
2
Order By: Relevance
“…22 Tiede et al demonstrated that the presence of anti-FVIII IgA was a strong negative predictor of recurrence-free survival after achieving partial remission. 18 In our study, no bleeding occurred between the decrease in the FVIII/W ratio and the subsequent clinical relapse, indicating that close monitoring of this parameter should be very useful for pre-emptive therapy. We propose that complete remission could be considered confirmed, there may be therapeutic consequences, such as more prolonged IST in case of non-normalization of the FVIII/W ratio or early re-treatment without waiting when the ratio falls.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…22 Tiede et al demonstrated that the presence of anti-FVIII IgA was a strong negative predictor of recurrence-free survival after achieving partial remission. 18 In our study, no bleeding occurred between the decrease in the FVIII/W ratio and the subsequent clinical relapse, indicating that close monitoring of this parameter should be very useful for pre-emptive therapy. We propose that complete remission could be considered confirmed, there may be therapeutic consequences, such as more prolonged IST in case of non-normalization of the FVIII/W ratio or early re-treatment without waiting when the ratio falls.…”
Section: Discussionsupporting
confidence: 54%
“…For detection of relapses, they also suggested that anti‐FVIII IgG could be a predictor of prognosis . Tiede et al demonstrated that the presence of anti‐FVIII IgA was a strong negative predictor of recurrence‐free survival after achieving partial remission …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is a useful screening test for screening for circulation anticoagulants. A previous study reported IgA subclass antibody as a poor prognostic marker in AHA (Tiede et al , ). However, details regarding antibody type was not included in our study.…”
Section: Discussionmentioning
confidence: 92%
“…2,4,14 Relapses have been reported in up to 23% of cases. 2,9,15,16 Although some factors have been associated with a better survival (age <60 years, non-malignant underlying conditions), 3,17 or the probability of obtaining a remission, 17,18 the long-term natural history of patients who relapse after initial complete response to IST and factors predisposing to relapse remain only partially addressed and not well understood. [2][3][4]7,[9][10][11] This retrospective study describes the relapse pattern and long-term outcome of a large cohort of patients affected by AHA.…”
mentioning
confidence: 99%